2019
DOI: 10.1007/s00381-019-04097-0
|View full text |Cite
|
Sign up to set email alerts
|

Experience with resorbable sonic pins for the attachment of distraction devices in posterior cranial vault distraction operations

Abstract: Background Distraction techniques are effective methods for the treatment of craniosynostoses when a significant gain of an intracranial volume is required. However, this technique raises some challenges at different stages of the treatment. While installing the distractors in patients with thin calvarial bone, there is a risk of dural damage from the titanium screws. The need for wide exposure of the devices and the screws during removal causes soft tissue damage and bleeding. Objective This study aimed to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…10,11 Eight studies computed the average intracranial volume gain using preoperative and postoperative computed tomography scans. 8,11,12,14,18,[20][21][22] In those studies, the average volume gain was 253.2 cm 3 . The average volume gain per mm of distraction was 9.8 cm 3 .…”
Section: Surgical Outcomesmentioning
confidence: 84%
See 2 more Smart Citations
“…10,11 Eight studies computed the average intracranial volume gain using preoperative and postoperative computed tomography scans. 8,11,12,14,18,[20][21][22] In those studies, the average volume gain was 253.2 cm 3 . The average volume gain per mm of distraction was 9.8 cm 3 .…”
Section: Surgical Outcomesmentioning
confidence: 84%
“…Various strategies have been employed to decrease this risk, including using resorbable material in the epidural space to act as a barrier between the dura and the screws, 5,35 using self-drilling screws, 17 using the shortest screws possible, 6 and using resorbable pins instead of titanium screws. 14 No comparative study has been published to establish the effectiveness of any of these maneuvers. Overall, we found that PCD has a complication rate of 32.2%, which is higher than calvarial vault remodeling (5-11%), 36 spring-assisted cranioplasty (7.4%) 37 and minimally-invasive suturectomy and helmet therapy (3.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In younger patients or instances of thin calvarium, the device can be stabilized with footplates of mesh covering the bone to reduce stress from pin fixation [28]. Resorbable fixation systems such as ultrasound-activated pins, heat-activated pins, sonic pins and conventional resorbable screws have been experimented with to obviate the need for a second procedure [28,29]. Sonic pins are accepted as reliable but may resorb too quickly for ossification during consolidation [28].…”
Section: External Devicesmentioning
confidence: 99%
“…At least four self-drilling, self-tapering titanium mini screws are used on each footplate. Additionally, biodegradable pins SonicWeld ® can be used to fix the devices replacing part or all of the titanium screws [ 2 , 13 ]. When inserting the screws, the dura is protected from perforation by placing dissector between the bone and the dura.…”
Section: Surgical Techniquementioning
confidence: 99%